Analisis Dan Perancangan Sistem Informasi Pengaduan Masyarakat Berbasis Android Pada Dinas Komunikasi Dan Informatika Kota Jambi - Juarsyah, Ishak; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
The communication and informatic kotajambi are required to follow the future to continue to innovate in public information on the community service .In the process of creating prosperity for the city government jambi realize the smart city in the form of public complaints .This research framework consisting of identification problems , a literature review , data collection , analysis and design , prototype design , and preparing reports .Method of development the writers do the diagram context , a diagram zero level zero , diagrams and level 1 prototype 1.0 process. By existence of public complaints through hopes will break make it easy between the community to send opd claims to.By the presence of the system of services community complaints, opd can control complaints and aspirations of directly.The prototype of research has produced a information system design community complaints based android from the local office of communication and informatic kotajambi. The research is an example of community complaints based information system android from the local office of communication and informatic kotajambi to the extent that when will be used by other organization needs to be adjusted to the needs of an organization concerned .The need to make adjustments on application against found on the real issues .The need for notifications for the reporter that the reporter know the status of the report in real time is it in will immediately follow up .The need for features that facilitates between admin or a person in charge of the complaints process for the community with a field officer.